Sampling root exudates – Mission impossible? - Oburger, Eva; Jones, David L. (Rhizosphere, 2018)
Accurate information about the quantity, quality and spatiotemporal dynamics of metabolite release from plant roots is vital to understanding the functional significance of root exudates in biogeochemical processes occurring at the root-microbe-soil-interface. Significant progress in analytical techniques nowadays allows us to gain a much better picture of the rich diversity of compounds that are present in root exudates, but ultimately the choice of exudation sampling strategy will determine the ecological significance of obtained exudation results. Unfortunately, in the past, little consideration has been given to the experimental strategy used to sample root exudates. To date, our knowledge on root exudation is mainly based on plants grown and sampled in nutrient solution culture (hydroponics). Despite the operational benefit of hydroponic systems, the question remains as to how ecologically relevant exudation results obtained under these artificial conditions are compared to soil environments, particularly in the context of exudate driven rhizosphere processes. The quantitative and qualitative measurement of root exudation in soil, however, is fraught with problems due to: (i) continual removal of exudates from solution by the microbial community; (ii) loss of exudates from solution due to their sorption to the solid phase; and (iii) simultaneous release of compounds from soil organic matter breakdown. While a perfect method for sampling root exudates does not exist, soil based approaches, if appropriately applied and interpreted, may still provide more realistic insights into exudation dynamics in natural soil environments. This review aims to provide an overview of different root exudation sampling approaches and their advantages and limitations to support the selection of the most suitable experimental procedure for any specific research question. We address critical methodological aspects that need to be considered in the choice of experimental approach, like growth and sampling medium (soil, hydroponic), sterility, sampling location (whole root system, individual root segments) as well as plant age, daytime, re-uptake of metabolites affecting duration and timing of the sampling event and data presentation. In addition, we summarize the main analytical approaches to analyze root exudates, ranging from liquid sample analysis to isotope tracking and imaging techniques.